2009
DOI: 10.4103/0970-9371.55222
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography-guided fine needle aspiration cytology of thoracic mass lesions: A study of 57 cases

Abstract: Background:Computed tomography (CT)-guided fine needle aspiration cytology (FNAC) is regarded as a rapid, safe, and accurate diagnostic tool in examining thoracic mass lesions for the last three decades.Aims:To assess the role of CT-guided FNAC in thoracic mass lesions, to analyse the results, and to compare the results with other studies.Materials and Methods:Fifty-seven patients were studied over a year (July 2007 to June 2008) for their age, sex, and topographic distribution, pleural infiltration (based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
41
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 5 publications
20
41
3
Order By: Relevance
“…7 CT guided FNAC of pulmonary masses provides a simple, easy, and reliable method for reaching rapid tissue diagnosis with minimal complication. 8 In the current study, most of the cases were male (74%), that's in agreement with the result of Saha et al, 8 Mondal et al 3 and others. 9,10 Age distribution of our cases was mostly in the sixth and seventh decade.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…7 CT guided FNAC of pulmonary masses provides a simple, easy, and reliable method for reaching rapid tissue diagnosis with minimal complication. 8 In the current study, most of the cases were male (74%), that's in agreement with the result of Saha et al, 8 Mondal et al 3 and others. 9,10 Age distribution of our cases was mostly in the sixth and seventh decade.…”
Section: Resultssupporting
confidence: 82%
“…The sensitivity and specificity of the present study were 98.46% and 99.2%, respectively. agreement with studies done by Monda et al and Saha et al 3,8 Squamous cell carcinoma was the most common malignant lesion, which was followed by adenoarcinoma and then small cell carcinoma. The incidence of adenocarcinoma was reported to be significantly higher than that of squamous cell carcinoma in recent studies by Tan et al 9 and Madan et al, 11 where as in certain other studies, prevalence of squamous cell carcinoma was more than adenocarcinoma.…”
Section: Resultssupporting
confidence: 82%
“…This was well corelated with studies of Tan KB et al where males were 71%, Bandyopadhyay A et al with 80.6% of males and Saha A et al having 78.9% males. [10][11][12] In this study, lung tumors were located more on the left side than on the right in contrast to the study of Santosh et al where in tumors were located more on right side. In our study, 64% were smokers and it's an established fact that smoking is strongly associated with lung cancer.…”
Section: Discussioncontrasting
confidence: 55%
“…In the present study, out of 55 cases 41 were men (74.5%) and 14 were women (25.45%) with a male : female ratio of 2.9 : 1, which was quite comparable to studies by Saha A et al 7 where male were 78.9 %, Sarkar RN et al 8 (77% male) and Jayashankar et al 9 ( 70%). However greater male ratio (85%) was seen in study by Mukherjee S et al 10 and lower by Gangopadhyay M et al 11 (59.8%) and Singh JP et al 12 (52%).…”
Section: Discussion:-supporting
confidence: 78%
“…The peak age of incidence (60-69 years) in the study was observed to be same as that of the peak age of incidence in two other studies done by Jayashankar et al 9 (60-69 years) and Basnet et al 13 (60-69 years). However, this peak age of incidence was a decade more than that documented in a study by Saha A et al 7 , in which peak age of incidence was in the range of 51-60 years. Most of the patients in this study were in the range of 40 -70 years which was similar to the study done by Mukherjee S et al 10 (40-70 years).…”
Section: Discussion:-contrasting
confidence: 47%